The Reluctance of Capitalizing the Borrowing Costs A Recent Study of Residence Development in the Province of Jawa Barat - Samuel Anindyo Widhoyoko (Universitas Agung Podomoro, 2017)
The emerging trend of emerging business occurs due to the consciousness of society regarding to the long-term investment. Many property developers are currently being aware of creating new spaces for society, as well as preparing their company to face new era of the pricing competition of property. This research focuses on the decision of property developers in pricing decision in the scope of construction cost reporting in which the bank loan would likely affect the financial leverage, project acceleration, and selling price which result in volume of profit. Based on the applicable accounting standards (PSAK no.26), companies are tocapitalize all borrowing costs to the construction costs at the same time. Using quantitative method, this research attempts to find relationship between construction cost and borrowing cost towards stock market performance. In this study, EPS is assumed to be a parameter for stock performance measurement. The study suggests that constructioncosts does not impact on the stock performance in the market. On the other hand, borrowing costs give significant impact to EPS. This research also finds that in any level of rate, interest would be influencing the EPS.